Corporate Social Responsibility: Is It A Strategy To Enhance Reputation? An Analysis into The Auto Industry - Mathew, Justy (2006)
Corporate Social Responsibility, Is it a strategy to enhance the reputation of corporations? Companies today have various methods to gain a favourable outlook in the minds of its stakeholders. Corporate Social Responsibility is one of the strategies that companies use in this regard.